2012
DOI: 10.1111/j.1399-3054.2011.01551.x
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial plant methane production and emission

Abstract: In this minireview, we evaluate all experimental work published on the phenomenon of aerobic methane (CH(4) ) generation in terrestrial plants and plant. Clearly, despite much uncertainty and skepticism, we conclude that the phenomenon is true. Four stimulating factors have been observed to induce aerobic plant CH(4) production, i.e. cutting injuries, increasing temperature, ultraviolet radiation and reactive oxygen species. Further, we analyze rates of measured emission of aerobically produced CH(4) in pect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 59 publications
1
73
0
Order By: Relevance
“…This is in accordance with the findings of Ghyczy et al 9,12 who demonstrated that endothelial cells from rat liver produced CH 4 when exposed to site-specific inhibitors of the ETC. It would seem that aerobic CH 4 formation is not only a result of chemical formation from dead biomass as previously shown by several studies 8,11 but might also have a physiological role in eukaryotic groups such as fungi, animals and plants. For example aerobic CH 4 formation may be an integral part of cellular responses towards changes in oxidative status present in all eukaryotes.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…This is in accordance with the findings of Ghyczy et al 9,12 who demonstrated that endothelial cells from rat liver produced CH 4 when exposed to site-specific inhibitors of the ETC. It would seem that aerobic CH 4 formation is not only a result of chemical formation from dead biomass as previously shown by several studies 8,11 but might also have a physiological role in eukaryotic groups such as fungi, animals and plants. For example aerobic CH 4 formation may be an integral part of cellular responses towards changes in oxidative status present in all eukaryotes.…”
Section: Discussionmentioning
confidence: 62%
“…Very recently it has been suggested 8 that the amino acid methionine might be a precursor for CH 4 formation in living plants. It is likely that methionine, a compound that also has a major role in sulphur metabolism and transmethylation reactions in fungi, might act as a precursor compound of CH 4 formation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations